Effects of progressive muscle relaxation training on negative emotions and sleep quality in COVID-19 patients: A clinical observational study - Xiao, Chun-Xiu (Medicine (Baltimore), 2020)
This study investigates the effect of progressive muscle relaxation training on negative mood and sleep quality in Coronavirus Pneumonia (COVID-19) patients. COVID-19 is an emerging infectious disease, and there is still uncertainty about when the outbreak will be contained and the effectiveness of treatments. Considering that this disease is highly contagious, patients need to be treated in isolation. This may lead to psychological symptoms such as anxiety and depression, and even sleep problems. This study is a clinical observation study. Participants included 79 COVID-19 patients admitted to a designated hospital for COVID-19 patients in Wuhan from February to March, 2020. Patients were selected and assigned to the control group and the observation group according to their wishes, with 40 and 39 cases in each group, respectively. The control group received routine treatment and nursing, and the observation group received progressive muscle relaxation training, in addition to the routine treatment and nursing. We compared scores of the Pittsburgh Sleep Quality Index Scale (PSQI), the Generalized Anxiety Disorder (GAD-7), and the Patient Health Questionnaire (PHQ-9) before and after the intervention. There was no significant difference in PSQI, GAD-7, and PHQ-9 scores between the control group and the observation group before the intervention (P > .05). After the intervention, the difference in scores of PSQI, GAD-7, and PHQ-9 in the 2 groups were statistically significant (P < .05). Progressive muscle relaxation training can significantly reduce anxiety and depression and improve sleep quality in COVID-19 patients during isolation treatment. Progressive muscle relaxation training was shown to improve the treatment effect of patients and is worthy of clinical promotion.